Systemic toxicity of CAR-T therapy and potential monitoring indicators for toxicity prevention - Li, Jingxian; Chen, Huiguang; Xu, Chaoping; Hu, Mengci; Li, Jiangping; Chang, Wei (Frontiers in Immunology, 2024)
Malignant tumors of the hematologic system have a high degree of malignancy and high mortality rates. Chimeric antigen receptor T cell (CAR-T) therapy has become an important option for patients with relapsed/refractory tumors, showing astonishing therapeutic effects and thus, it has brought new hope to the treatment of malignant tumors of the hematologic system. Despite the significant therapeutic effects of CAR-T, its toxic reactions, such as Cytokine Release Syndrome (CRS) and Immune Effector Cell-Associated Neurotoxicity Syndrome (ICANS), cannot be ignored since they can cause damage to multiple systems, including the cardiovascular system. We summarize biomarkers related to prediction, diagnosis, therapeutic efficacy, and prognosis, further exploring potential monitoring indicators for toxicity prevention. This review aims to summarize the effects of CAR-T therapy on the cardiovascular, hematologic, and nervous systems, as well as potential biomarkers, and to explore potential monitoring indicators for preventing toxicity, thereby providing references for clinical regulation and assessment of therapeutic effects.